Problems and Developments in the Core Theory of International Business - Buckley, Peter J. (Journal of International Business Studies, 1990)
The established theory of international business is not without problems. It is necessary to specify the key relationship between internalisation and market structure and between internalisation and competitive advantage more carefully. This paper attempts to clarify the former relationship by reference to the work of Hymer and the latter by contrasting the nature of internalisation decisions with those building short-run competitive advantage. Avenues of development of the theory include the integration of nontraditional concepts and the reintegration of areas of research that have become divorced from core international business theory.